2008
DOI: 10.1017/s002531540800057x
|View full text |Cite
|
Sign up to set email alerts
|

Spawning and fecundity of Jenyns's sprat, Ramnogaster arcuata, a winter spawner in the temperate waters of the Río de la Plata estuary, Argentina–Uruguay

Abstract: The reproductive biology of the Jenyns's sprat Ramnogaster arcuata in the Río de la Plata area was studied using macroscopic and histological analysis of ovaries. Samples were collected during two research surveys carried out in June 1998 and June 1999. In addition monthly occurrences of this species from historical data were analysed. Jenyns's sprat specimens were mainly observed in open waters of the estuary during winter months. Most of the females collected during June 1998 and 1999 were in the spawning st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
1
11
1
Order By: Relevance
“…As far as we know, this represents the first contribution to fecundity estimates for the species. These values were higher when compared with those obtained for R. arcuata (570-2,026; 75-116 mm TL) (Rodrigues et al, 2008), but lower than the Buenos Aires stock of E. anchoita (Pájaro et al, 1997) (13,675 +/-856; 100-189 mm TL). The relative fecundity values ranged from 127 to 422 yolked oocytes per female gram (ovary free).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…As far as we know, this represents the first contribution to fecundity estimates for the species. These values were higher when compared with those obtained for R. arcuata (570-2,026; 75-116 mm TL) (Rodrigues et al, 2008), but lower than the Buenos Aires stock of E. anchoita (Pájaro et al, 1997) (13,675 +/-856; 100-189 mm TL). The relative fecundity values ranged from 127 to 422 yolked oocytes per female gram (ovary free).…”
Section: Discussionmentioning
confidence: 52%
“…The oocyte diameter distribution of A. marinii showed four clutches/ groups of oocytes easily differentiable in histological slides (between 50 and 650 µm) and ovaries displayed a continuous distribution from primary growth to advanced yolked oocytes. In R. arcuata, Rodrigues et al (2008) found five groups of oocytes. The first four groups, as in A. marinii, showed a continuous distribution and were composed of primary growth oocytes, cortical alveolus stage, early yolked oocytes and advanced yolked oocytes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, batch fecundity estimated of Anchoa marinii was 749 to 3,207 oocytes, (López et al, 2013). Rodrigues et al (2008) reported a batch fecundity of 570-2,026 oocytes for Ramnogaster arcuata specimens. Pájaro et al (1997) reported a fecundity of 13,675 oocytes (+/-856) for Engraulis anchoita.…”
Section: Discussionmentioning
confidence: 99%
“…However, when comparing the relative fecundity of these species, it is noticeable that B. aurea presented the lowest values in comparison with those of the above mentioned species: 41-381 hydrated oocytes per gram of female (ovary free) for B. aurea, 127-422 oocytes for A. marinii (López et al, 2013); R. arcuata between 150 and 437 oocytes (Rodrigues et al, 2008) and E. anchoita with 574 oocytes (Pájaro et al, 1997). These differences could be due to the largest size of the hydrated oocytes of B. aurea (1000 to 1600 μm in this paper), in comparison with other local species of Clupeiformes (A. marinii; R. arcuata and E. anchoita) which are less than 1000 μm (Rodrigues et al, 2008;López et al, 2013;Pájaro et al, 1997). The size and number of eggs produced vary greatly among species and all of these traits have important consequences for survival.…”
Section: Discussionmentioning
confidence: 99%